Muscle strength in breast cancer patients receiving different treatment regimes - Klassen, Oliver; Schmidt, Martina; Ulrich, Cornelia; Schneeweiss, Andreas; Potthoff, Karin; Steindorf, Karen; Wiskemann, Joachim (Journal of cachexia, sarcopenia and muscle, 2017)
Background Muscle dysfunction and sarcopenia have been associated with poor performance status, an increased mortality risk, and greater side effects in oncologic patients. However, little is known about how performance is affected by cancer therapy. We investigated muscle strength in breast cancer patients in different adjuvant treatment settings and also compared it with data from healthy individuals. Methods Breast cancer patients (N = 255) from two randomized controlled exercise trials, staged 0-III and aged 54.4 ± 9.4 years, were categorized into four groups according to their treatment status. In a cross-sectional design, muscle function was assessed bilaterally by isokinetic dynamometry (0°, 60°, 180°/s) as maximal voluntary isometric contraction (MVIC) and maximal isokinetic peak torque (MIPT) in shoulder rotators and knee flexors and extensors. Additionally, muscular fatigue index (FI%) and shoulder flexibility were evaluated. Healthy women (N = 26), aged 53.3 ± 9.8 years, were tested using the same method. Analysis of covariance was used to estimate the impact of different cancer treatments on skeletal muscle function with adjustment for various clinical and socio-demographic factors. Results Consistently, lower muscle strength was measured in shoulder and knee strength in patients after chemotherapy. On average, patients had up to 25% lower strength in lower extremities and 12-16% in upper extremities in MVIC and MIPT during cancer treatment compared with healthy women. No substantial difference between patient groups in shoulder strength, but significantly lower shoulder flexibility in patients with radical mastectomy was measured. Chemotherapy-treated patients had consistently higher FI%. No serious adverse events were reported. Conclusions Breast cancer patients showed markedly impaired muscle strength and joint dysfunctions before and after anticancer treatment. The significant differences between patients and healthy individuals underline the need of exercise therapy as early as possible in order to prevent or counteract the loss of muscle function after curative surgery as well as the consequences of neo-/adjuvant chemotherapy.
First published: 28 November 2016
Gesehen am 23.10.2018